The Relationship between Menstrual Knowledge and Readiness to Face Menarche in Grade III-V Students at SDN 158 Babakan Sari - Yani, Tri Ardayani (Journal of health research and technology, 2026)
The menarche process is a physical and emotional change experienced by school-age children. Readiness to face menarche is associated with the level of student knowledge. The average age of menarche at school age occurs at 12-14 years. Readiness and information about menarche and menstruation are needed. To determine the relationship between menstrual knowledge and readiness to face menarche in grade III-V female students at SDN 158 Babakan Sari. Quantitative research method with cross sectional approach. There are two questionnaires used, namely menstrual knowledge questionnaire and readiness questionnaire for menarche. The population is female students in grades III-V, the sample of this study is 127 respondents with stratified sampling technique. Data analysis using chi square test. Level of knowledge of students regarding menstruation, the majority have less knowledge related to menstruation, almost half of the female students have less knowledge about menstruation (47.2%). Half of the respondents are not ready to face menarche, which is (61.4%). There is a relationship between knowledge of menstruation and readiness to face menarche (p = 0.000 < 0.005). There is a relationship between menstrual knowledge and readiness to face menarche in grade III-V female students at SDN 158 Babakan Sari. So it is recommended that information about menstrual knowledge be given since grade III. It is hoped that adolescent girls will increase their knowledge to obtain information about menstruation, so that adolescent girls are better prepared to face menarche.